PERAN VARIABEL KOMITMEN ORGANISASI DAN INOVASI PADA HUBUNGAN PENGANGGARAN DAN KINERJA: STUDI KASUS PADA SKPD KABUPATEN MAGELANG - Kunwaviyah, Kunwaviyah; Syafruddin, Muchamad (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2010)
This study aims to examine the budgetary participation and performance relationship in apublic sector organization. It also attempts to examine whether organization commitment andperception of innovation mediate the budgetary participation and performance relationship.To collect data of this study, survey questionnaires are used. From 160 questionnaires weregiven to managers in a public sector organization, questionnaires with complete answers were58 questionnaires (36.25%). A path analysis was utilized to examine the direct and indirecteffects of budgetary participation on managerial performance.The analysis results indicate thatbudgetary participation and managerial performance have positive relationship and statisticallysignificant. Budgetary participation also directly affects organization commitment and perceptionof innovation. But budgetary participation did not indirectly affect managerial performance viathe intervening variables of organization commitment and perception of innovation.